Pemanfaatan Kotoran Ternak Sebagai Sumber Energi Alternatif di Kelompok Ternak Sapi Potong Sido Makmur Umbulsari Jember - Nurkholis Nurkholis; Suluh Nusantoro; Aan Awaludin; M. Adhyatma; Bagus Djuni (Journal of Community Development, 2021)
The sustainability of the livestock business does not only depend on the success of the maintenance system which aims at increasing productivity, but also on the ability to process the resulting livestock waste. Livestock waste is the main source of quality degradation for the environment, this occurs due to the presence of ammonia and methane gas which is formed from the decomposition of organic matter. Ammonia along with other gases can cause acid rain, while methane gas causes a greenhouse effect. This community service partner is a farmer who is part of the "Sido Makmur" beef cattle group in Umbulrejo village, Umbulsari sub-district, Jember district. The purpose of this community service activity is to transfer knowledge and technology regarding livestock waste processing to be used as biogas. The selection of waste treatment topics is based on a situation analysis of the "Sido Makmur" livestock group. The results of the situation analysis show that generally livestock manure is not processed and is left around the stables and there are some group members who have difficulty buying LPG fuel because it is considered quite expensive. The implementation of the service consists of several activitie, the first was outreach activities, demonstrations / practices and assistance of community service activities. The results of the community service survey which have shown that the application of technology in the processing or utilization of livestock manure into a useful material that even has economic value will support the creation of an environmentally friendly livestock system or zerro waste system, besides that it will also improve the welfare of breeders through minimizing the cost of purchasing fuel.